Rancang Bangun Sistem Informasi Pelayanan Jasa Home Service Dengan Model Waterfall Pada CV. Gian Motor Autoservice - Eko, Giyan; Yunita, Yunita; Amalia, Hilda (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract – Transportation is needed by humans as the times develop and there is an increase in mobility of activities. The development of motorized vehicles every year is increasing and diverse. Of course, the increasing number of vehicles, the more people who need service or repair services they have. In the current era, it requires the use of technology. The technology that is widely used is web-based technology, the web is used by thousands of people as a good promotional media. In designing information systems a model that can be used is needed, the selection of the right model is an important factor in the success of building a system. The Waterfall Model is a simple model and is suitable for developing software with specifications that do not change. So with the waterfall methode is able to complete the design of service information system home service. Keyword: information system, home service, waterfall